50 Global Actions to Manage the COVID-19 Infodemic: A WHO Framework. (20th October 2021) - Mahajan, A; Phuong, L; Nguyen, T; Czerniak, C; Lamichhane, J; Purnat, T; Briand, S
Abstract: Issue: The World Health Organization describes an infodemic as an "overabundance of information - good or bad - that makes it difficult for people to make decisions for their health." Description of the problem: On April 7-8, 2020, the WHO Information Network for Epidemics (EPI-WIN) held a global online to crowdsource ideas from an interdisciplinary group of experts to form a novel COVID-19 infodemic response framework. The online consultation comprised of four plenary sessions and a brainstorming session conducted entirely online. Nearly 1500 individuals from over 100 countries and territories spanning social scientists, epidemiologists, staff from ministries of health and institutes of public health, registered for the consultation. Results: A set of 50 proposed actions for a framework for managing infodemics in health emergencies was developed that will provide guidance for governments and public health institutions to take in five key areas of action that emerged from the consultation: strengthening evidence and information simplifying and explaining what is known fact-checking and addressing misinformation amplifying messages and reaching the communities and individuals who need the information quantifying and analysing the infodemic, including information flows, monitoring the acceptance of public health interventions, and assessing factors affecting behaviour at individual and population levels strengthening systems for infodemic management in health emergencies Lessons: Everyone has a role to play Read the Call for Action Sign the Call for Action https://www.who.int/news/item/11-12-2020-call-for-action-managing-the-infode Key messages: The confusion due to Infodemic can lead people to ignore public health measures and take risks that can cause serious harm. Recognizing this WHO convened an interdisciplinary group of experts 7-8 April 2020 virtually to form a novel COVID-19 infodemic response framework.